Study of Mobile data management and Optimization Techniques - Ms Jyoti; Ms. Yogita (Innovative Research Thoughts, 2023)
Mobile data management is a complex field that ensures data efficiency on mobile devices and networks. Data synchronisation between devices and servers ensures platform consistency. Caching and prefetching improve mobile device performance by storing frequently used data. In low-connectivity areas, data compression improves bandwidth use and lowers data transmission costs. Context-aware data management considers location, time, and user behaviour to give relevant info. Encryption and access control safeguard user data. Offline data access lets mobile applications work offline and sync with servers when connected. Mobile data analytics uses massive amounts of user data to improve user experience and inform choices. Data backup and recovery guarantee data recovery after loss or device failure. Data de-duplication optimises storage and retrieval. Data governance enforces legislation and industry standards for data access, use, and retention. Mobile data management ensures efficient, safe, and reliable data services on mobile platforms while optimising resource consumption and user experience. It underpins current mobile apps and services.